(untitled) (Research, Society and Development, 2021)
It was found in this article how the phenomenon of school dropout has been unveiled within the scope of the Federal Network of Professional, Scientific and Technological Education. In the qualitative study, bibliographic and documentary research was used to support the construction of a panorama of studies on the problem. The results showed that the researchers conceptualized school dropout as the loss of link between student and educational institution. The motivational factors identified as promoters of school dropout were: lack of adaptation to academic life, disenchantment or demotivation with the chosen course, poor learning capacity and study skills, didactic-pedagogical issues, academic management of the course and economic and social context. The intervention proposals were presented through welcoming actions directed to incoming students and monitoring of school performance. It can be concluded that diagnoses of motivational factors for school dropout are necessary to mitigate their effects, as well as direct the construction of intervention proposals.